PKM Peduli Kesehatan Mental melalui Konseling Kelompok di Madrasah Tsanawiyah Madani Makassar - Sulaiman, Dwi Rezky Anandari; Lamada, Mustari; Dewi, Shabrina Syntha; Ashadi, Nini Rahayu; Suwahyu, Irwansyah (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This article explores efforts to improve students' awareness of mental health issues through group counseling training. The group counseling training focuses on the development of counseling programs aimed at providing a deeper understanding of the importance of mental health. The training involved 24 student representatives from Madrasah Tsanawiyah Madani Makassar. The training methodology employed a structured learning approach with stages of preparation, assessment, implementation, and evaluation (3PE). The training results indicate that students understand the importance of mental health issues, and through the provided simulations, students are able to engage in group counseling. Group counseling programs can be an effective strategy in building awareness and support for mental health within the school environment.